Reflex modulation during rhythmic limb movements in humans - Tomoyoshi Komiyama; Tsuyoshi Nakajima (Japanese Society of Physical Fitness and Sports Medicine, 2012)
For many locomotor behaviors, such as walking or running, we count on subliminal somatosensory information to smoothly maintain on-going movement and avoid falling down when disturbances are presented to the stability of the body. Reflex responses induced by disturbances to stability play important roles in generating quick corrective responses. Reflex outputs to the arm and leg muscles generated by muscle and cutaneous afferents during locomotor movement show quite different features compared to those generated by simple voluntary contraction during sitting or standing, irrespective of the similar background activity of motoneurons. In particular, the excitability of cutaneous reflex pathways elicited by the electrical stimulation of low threshold mechanoreceptors on the skin is strongly modulated in a phase-, nerve-, task-dependent manner during locomotor movement. The pattern generating system in the spinal cord, which has been studied intensively in quadrupedal animals, may be responsible for both generating locomotor movement and reflex modulation even in humans. However, due to methodological difficulties, the accumulated evidence derived from human experiments is indirect. In this review, we will outline these unique features of the cutaneous reflexes during locomotor and rhythmic movements in humans.